Bacteriophages- A New Frontier in Medicine - Aryamaan Sethi; Madhu Y; Aishwarya Mantri; Shubham Jaju (International Journal of Virus Studies, 2024)
Bacteriophages, or phages, are viruses that specifically target and infect bacteria, offering an innovative alternative to traditional antibiotic treatments, especially in the face of rising antibiotic resistance. The resurgence of phage therapy has been driven by the increasing prevalence of multidrug-resistant bacterial strains and the slowdown in the development of new antibiotics. Phages, unlike antibiotics, target specific bacterial strains, reducing the impact on the natural microbiota and potentially offering a safer and more precise treatment. However, the clinical application of bacteriophages presents several challenges. One major issue is bacterial resistance to phages, similar to antibiotic resistance. Bacteria can evade phages by altering receptors or employing defense mechanisms to block phage DNA injection. Another concern is phage-induced lysis, which may release harmful bacterial toxins into the body. Additionally, phages can transmit genetic material, such as virulence factors or antibiotic resistance genes, to the microbiome, which brings up potential safety issues. Another challenge is the immune system's response to bacteriophages, as the body might identify them as foreign agents and remove them before they can perform their intended function. The specificity of phages, while advantageous in reducing harm to non-target bacteria, complicates treatment, requiring personalized phage cocktails tailored to each infection, making standardization and large-scale production difficult. Despite these hurdles, bacteriophage therapy holds significant promise as a complementary or alternative approach to antibiotics, particularly in addressing infections that no longer respond to conventional treatments. Ongoing research and clinical trials are critical to understanding and mitigating the limitations of phage therapy to integrate it successfully into modern medical practice​.
Keywords: Bacterial resistance; Bacteriophage; Multi-drug-resistant bacteria; Phage therapy; Specificity; virus